TAFSIR JAMAâI UNTUK PENCERAHAN UMMAT - Hidayat, Syamsul (Kopertais Wilayah X Jawa Tengah, 2017)
This study aims to examine the interpretation of At-Tanwir, published by theMuhammadiyah Central Executive, by looking at his position in the map of the studyÂ of Qurâanic commentary in present-day Indonesia. î e study focused on the form,Â method and style of interpretation used by the interpretation.According to several studies conducted by Howard M. Federspiel, Islah Gusmian andÂ Ahmad Arif Junaidi, the study of the Qurâanic commentary in Indonesia that hasÂ grown long enough, even since the entry of Islam in Indonesia, begins with a study ofÂ the Arabic tafsir classic, later developed into the writing of the tafsir books in Arabic,Â Malay (Indonesian), as well as interpretations in several regional languages. Diff erentÂ forms of interpretation, methods and styles. However, more is the interpretation of bilÂ raâyi, by the method of ijmali and tahlily, by combining linguistic complexities, legalÂ fiqh, theology, and social culture literature. Nevertheless, there is also a very limitedÂ number of maudhuâi (tematic) interpretations. In general, the book of exegesis isÂ written by individuals (tafsir fardi) and a little interpretation written by the team inÂ institutional (tafsir jamaâi).Tafsir at-Tanwir attempts to interpret the Quran with the principle of responsiveness, awakening the dynamics, generating ethos: the ethos of worship, the economic ethos,the social ethos, and the scientiÃ« c ethos. However, the weakness of this Tafsir At-TanwirÂ does not or has not expressed the characteristics of this exegesis as compared with otherÂ interpretations as it is done by the interpretation of the Ministry of Religious Aff airs, which provides a description in the Preamble which is recorded in a special volume, so that the reader must be careful in groping model and content of this book of exegesis.